Multimodal pce copolymers and use in cementitious mixtures
Patent Information
- Application Number
- CN202580021069.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-13
- Filing Date
- 2025-03-27
- Publication Date
- 2026-10-16
AI Technical Summary
此外,基于纤维素起始材料中天然存在的变化,水泥质混合物中纤维素醚的性能可有很大差异
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] This application relates to the fields of concrete, mortar, plaster and stucco. Background Technology
[0002] Concrete, mortar, plaster, and stucco (called cementitious mixtures) are typically prepared in two stages. First, a dry mixture containing cement, filler, and solid particulate additives (“dry components”) is blended together. Second, water is added to the dry mixture to create a wet mixture, which can be further formulated into the final cementitious mixture. The dry mixture is stable as long as it remains sufficiently dry; it can be stored for long periods and is easy to transport. The wet mixture begins to harden upon the addition of water and must be used before it becomes difficult to work with.
[0003] The main components of dry mixtures are fillers and cement. Dry mixture components may also include small amounts of other additives, such as water-reducing agents, water-retaining agents, organic binders, starch ethers, fibers, air-entraining agents, curing accelerators, curing retarders, defoamers, and pigments.
[0004] The amount of water added to prepare the wet mortar mixture is selected to provide a workable viscosity. The viscosity of the wet mortar mixture should allow it to be poured into molds or templates or spread smoothly on a substrate without dripping, and allow the cementitious mixture to conform to and adhere to the tiles or other materials pressed upon it. For example, the tiling mortar wet mortar mixture must be spread on the substrate with a trowel, held in place without dripping, and retain sufficient compressibility so that when a tile is pressed into the wet mortar, the mixture will deform to fully contact and adhere to the back surface of the tile. The more contact with the back surface of the tile, the better the tile adhesion after the mortar has cured.
[0005] Water-retaining agents prevent water from settling or otherwise separating from the dry components in a wet mixture. In this way, water-retaining agents improve cement hydration and the curing of the wet mixture, improve the adhesion of the wet mixture to the substrate, and control the drying time and processability of the wet mixture. Useful water-retaining agents should prevent water separation without impairing the processability of the wet mixture as previously described.
[0006] The most common water-retaining agent is cellulose ether. Cellulose ether is produced through energy-intensive, high-waste processes. Furthermore, the properties of cellulose ether in cementitious mixtures can vary considerably due to variations naturally occurring in the cellulose starting materials.
[0007] The aim is to identify alternative water-retaining agents that provide the same (or better) water retention and processability as existing water-retaining agents and can be produced with consistent quality through a simple, low-waste process. Summary of the Invention
[0008] Poly(carboxylic acid ether) copolymers (PCE copolymers) comprise multiple polyethylene glycol (PEG) polymer or oligomer chains dangling from an acidic backbone polymer. Ester bonds connect the PEG chains to the backbone polymer. This structure is often referred to as a "comb" structure, and is described by the acidic backbone polymer acting as the ridges of the comb and the dangling PEG chains attached to the backbone as the teeth of the comb.
[0009] PCE copolymers are sometimes added to cementitious mixtures as water-reducing agents, but they are not considered water-retaining agents. Water-reducing agents (also known as plasticizers or superplasticizers) are different from water-retaining agents. Water-reducing agents allow cementitious mixtures to maintain a workable viscosity with less water, but they generally do not improve water retention.
[0010] Ester bonds in PCE copolymers can be hydrolyzed to release dangling PEG chains and recover the acidic backbone polymer of the PCE copolymer in the form of a poly(carboxylic acid) polymer. For the purposes of this document, the poly(carboxylic acid) polymer obtained by hydrolyzing the ester bonds of a PCE copolymer is referred to as a "hydrolysis product polymer" or "HPP". We assume that the molecular weight distribution of the HPP of the PCE copolymer is approximately equal to the stoichiometric distribution of the acidic polymer backbone in the corresponding PCE copolymer.
[0011] We have found that certain multimodal PCE copolymers are effective as water-retaining agents in wet mixtures and provide processability that is approximately equal to (or better than) that of cellulose ethers. As used herein, “multimodal” means that the HPP of a PCE copolymer comprises a higher molecular weight (HMW) component and a lower molecular weight (LMW) component. As used herein, the weight-average molecular weight (Mn) of the “higher molecular weight (HMW) component” is... w The weight-average molecular weight (MAM) of the "lower molecular weight (LMW) component" is higher than that of the "lower molecular weight (LMW) component". As used herein, the weight-average molecular weight (MMA) of the "lower molecular weight (LMW) component" is... w The weight-average molecular weight is lower than that of the "higher molecular weight (HMW) component". We speculate that the presence of HMW and LMW components in HPP indicates that the PCE copolymer from which it originates also contains a higher molecular weight (HMW) component with a longer acidic backbone polymer and a lower molecular weight (LMW) component with a shorter acidic backbone polymer.
[0012] Multimodal PCE copolymers can be produced with consistent quality through emulsion polymerization.
[0013] One aspect of the present invention is a multimodal poly(carboxylic acid ether) (PCE) copolymer comprising repeating units derived from:
[0014] (a) 10 to 60 wt% (wt%) of (meth)acrylic acid monomers;
[0015] (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety comprises an average of 1 to 3.5 carbon atoms; and
[0016] (c) 5% to 40% by weight of PEG monomers, each of which independently contains:
[0017] (i) The (meth)acrylate moiety, which is linked via an ester bond to (ii) below.
[0018] (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and
[0019] (iii) An end portion of the polyethylene glycol portion connected at the end opposite to the (meth)acrylate portion, the end portion being selected from the hydrogen or alkyl portion; and
[0020] (d) 0% to 20% by weight of other unsaturated monomers
[0021] Wherein (i) weight percentage is based on the total weight of the PCE copolymer, (ii) the PCE copolymer comprises an acidic polymer backbone connected by ester bonds to multiple dangling polyethylene glycol side chains; and (iii) hydrolysis of the ester bonds in the PCE copolymer produces a poly(carboxylic acid) polymer with a multi-peak molecular weight distribution (referred to as "hydrolysis product polymer" or "HPP").
[0022] A second aspect of the invention is a poly(carboxylic ether) (PCE) copolymer comprising repeating units derived from:
[0023] (a) 10 to 60 wt% (wt%) of (meth)acrylic acid monomers;
[0024] (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety comprises an average of 1 to 3.5 carbon atoms; and
[0025] (c) 5% to 40% by weight of PEG monomers, each of which independently contains:
[0026] (i) The (meth)acrylate moiety, which is linked via an ester bond to (ii) below.
[0027] (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and
[0028] (iii) An end portion of the polyethylene glycol portion connected at the end opposite to the (meth)acrylate portion, the end portion being selected from the hydrogen or alkyl portion; and
[0029] (d) 0% to 20% by weight of other unsaturated monomers
[0030] Wherein (i) the weight percentage is based on the total weight of the PCE copolymer, (ii) at least 50% by weight of the PCE copolymer is soluble in a solution of tetrahydrofuran / formic acid (THF-FA; 100 / 5 volume / volume ratio) at a concentration of about 1 mg / mL, and (iii) the PCE copolymer has a dispersibility of at least 6.0 (M). w / M n ), such as by SEC in a solution of tetrahydrofuran / formic acid (THF-FA; 100 / 5 volume / volume ratio) according to the test method.
[0031] A third aspect of the present invention is a method for preparing poly(carboxylic acid ether) (PCE) copolymers, the method comprising emulsion polymerization of the following substances in an aqueous medium:
[0032] (a) 10% to 60% by weight of (meth)acrylic acid monomer;
[0033] (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety comprises an average of 1 to 3.5 carbon atoms; and
[0034] (c) 5% to 40% by weight of PEG monomers, each of which independently contains:
[0035] (i) The (meth)acrylate moiety, which is linked via an ester bond to (ii) below.
[0036] (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and
[0037] (iii) An end portion of the polyethylene glycol portion connected at the end opposite to the (meth)acrylate portion, the end portion being selected from the hydrogen or alkyl portion; and
[0038] (d) 0% to 20% by weight of other unsaturated monomers
[0039] The aqueous medium contains an emulsion amount of surfactant and a polymerization initiator, wherein (i) the weight percentage is based on the total weight of the monomers; (ii) the emulsion polymerization is carried out in at least two stages; and (iii) at least one stage of polymerization is carried out in the presence of at most 0.1% by weight of a chain transfer agent, and (ii) at least one stage of polymerization is carried out in the presence of at least 0.4% by weight of a chain transfer agent.
[0040] A fourth aspect of the invention is an aqueous dispersion comprising polymer particles suspended in an aqueous medium, wherein the polymer particles comprise a PCE copolymer as described in the first or second aspect of the invention.
[0041] A fifth aspect of the invention is a cementitious mixture comprising the following dry components (a)-(c):
[0042] (a) Packing material;
[0043] (b) Cement;
[0044] (c) at least 0.01% by weight of the PCE copolymer as described in the first or second aspect of the invention, based on the total weight of the dry components; and
[0045] The optional location also contains water.
[0046] A sixth aspect of the present invention is a cured cementitious mixture comprising:
[0047] (a) Packing material;
[0048] (b) hardened cement; and
[0049] (c) PCE copolymers as described in the first or second aspect of the present invention, or hydrolysis products thereof.
[0050] Multimodal PCE copolymers act as water-retaining agents. They can be used alone or in combination with other water-retaining agents and can completely or partially replace cellulose ethers for this purpose. Some embodiments can further provide wet mixtures with improved water retention and processability. Detailed Implementation
[0051] PCE copolymers and their synthesis
[0052] This invention relates to multimodal PCE copolymers. In an acidic aqueous environment, the PCE copolymer can exist as a dispersion of polymer particles suspended in an aqueous medium. In an alkaline aqueous environment, the carboxylic acid moiety in the PCE copolymer becomes charged, and the PCE copolymer swells and can dissolve in the aqueous phase. Depending on the concentration of dissolved polymer, the viscosity of the aqueous phase can increase.
[0053] PCE copolymers contain repeating units derived from (meth)acrylic acid monomers, (meth)acrylic acid alkyl ester monomers, and PEG monomers.
[0054] As used herein, "(meth)acrylic acid" refers to acrylic acid, methacrylic acid, or a mixture of both. In some embodiments, the (meth)acrylic acid monomer is substantially composed of acrylic acid. In some embodiments, the (meth)acrylic acid monomer is substantially composed of methacrylic acid. In some embodiments, the (meth)acrylic acid monomer is a mixture comprising acrylic acid and methacrylic acid, wherein methacrylic acid comprises at least 10% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight. In some embodiments, the (meth)acrylic acid monomer is a mixture comprising acrylic acid and methacrylic acid, wherein acrylic acid comprises at least 10% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight. In some embodiments, the (meth)acrylic acid monomer may also contain small amounts of other alkyl acrylic acids; in some embodiments, the concentration of other alkyl acrylic acids is at most 10% by weight or at most 5% by weight or at most 2% by weight or at most 1% by weight or substantially 0% by weight (no measurable concentration).
[0055] Similar to (meth)acrylic acid, "(meth)acrylate" refers to an acrylate portion, a methacrylate portion, or a mixture of both. The (meth)acrylate portion may have embodiments equivalent to those described for the (meth)acrylic acid monomer.
[0056] As used herein, “polyethylene glycol” or “PEG” refers to an oligomer or polymer containing, on average, more than one repeating ethylene oxide unit. Some embodiments of the PEG portion can be represented by the following formula:
[0057] -(CR 3 H-CH2-O-) n -
[0058] Where "n" represents an epoxide unit (CR) 3 The number of H-CH2-O-), and each R 3 Independently, it is a hydrogen or lower alkyl group. In the PEG portion, more than 50 molar percentage of the alkyl oxide unit is ethylene oxide, and R 3 On average, it contains less than 0.5 carbon atoms. In some implementations, R 3The PEG contains, on average, at most 0.3 carbon atoms, at most 0.2 carbon atoms, at most 0.1 carbon atoms, at most 0.05 carbon atoms, at most 0.02 carbon atoms, or 0.00 carbon atoms. In some embodiments, at least 70 mole percent, at least 80 mole percent, at least 90 mole percent, at least 95 mole percent, or at least 98 mole percent of the epoxide units in the PEG are ethylene oxide units. In some embodiments, 100 mole percent of the epoxide units in the PEG are ethylene oxide units. In some embodiments, the epoxide units other than ethylene oxide units are selected from propylene oxide units or butane oxide units.
[0059] In some embodiments, the PEG contains, on average, at least 2, 4, 5, 7, 9, 10, 12, 13, 15, 17, or 19 epoxide units. In some embodiments, the PEG contains, on average, at most 50, 45, 40, 30, 25, 23, or 20 epoxide units. Embodiments with the numeral "n" reflect these embodiments.
[0060] Based on the total weight of the PCE copolymer, the PCE copolymer contains 10% to 60% by weight of repeating units derived from (meth)acrylic acid monomers. In some embodiments, the PCE copolymer contains at least 15% by weight, or at least 20% by weight, or at least 22% by weight, or at least 24% by weight, or at least 25% by weight, or at least 27% by weight, or at least 28% by weight, or at least 30% by weight, or at least 32% by weight, or at least 35% by weight of repeating units derived from (meth)acrylic acid monomers. In some embodiments, the (meth)acrylic acid monomers primarily comprise (greater than 50% by weight) methacrylic acid.
[0061] Based on the total weight of the PCE copolymer, the PCE copolymer contains 30% to 70% by weight of repeating units derived from alkyl (meth)acrylate monomers. The alkyl (meth)acrylate monomers comprise alkyl moieties linked to the (meth)acrylate moieties via ester moieties. The alkyl moieties of the alkyl (meth)acrylate monomers contain an average of 1.0 to 3.5 carbon atoms. The (meth)acrylate moieties of the alkyl (meth)acrylate monomers have the previously described characteristics.
[0062] In some embodiments, the alkyl moiety contains, on average, at most 3.2 carbon atoms, at most 3.0 carbon atoms, at most 2.8 carbon atoms, at most 2.6 carbon atoms, at most 2.4 carbon atoms, at most 2.2 carbon atoms, or at most 2.0 carbon atoms. In some embodiments, the alkyl moiety contains, on average, at least 1.2 carbon atoms, at least 1.4 carbon atoms, at least 1.6 carbon atoms, at least 1.8 carbon atoms, or at least 2.0 carbon atoms. In some embodiments, the alkyl moiety in at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or up to 100% by weight of the (meth)acrylate monomer is selected from methyl and ethyl groups. In some embodiments, the alkyl moiety in at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or up to 100% by weight of the (meth)acrylate monomer is an ethyl group. In some embodiments, the alkyl moiety in a minority of the (meth)acrylate alkyl monomer may contain three or more carbon atoms, such as propyl, butyl, and hexyl groups. In some embodiments, up to 50% by weight, up to 40% by weight, up to 30% by weight, up to 20% by weight, up to 10% by weight, or 0% by weight of the (meth)acrylate alkyl monomer contains three or more carbon atoms in its alkyl moiety.
[0063] Examples of suitable alkyl methacrylate monomers include methyl acrylate, ethyl acrylate, methyl methacrylate, and ethyl methacrylate. In some embodiments, the alkyl methacrylate monomer comprises primarily (greater than 50% by weight) ethyl acrylate or at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or up to 100% by weight of ethyl acrylate. In some embodiments, the alkyl methacrylate monomer may comprise a mixture of alkyl methacrylate monomers, and in some embodiments, the alkyl methacrylate monomer consists essentially of a single monomer.
[0064] In some embodiments, the PCE copolymer contains at least 35% by weight, or at least 40% by weight, or at least 45% by weight, or at least 48% by weight, or at least 50% by weight of repeating units derived from alkyl (meth)acrylate monomers. In some embodiments, the PCE copolymer contains at most 65% by weight, or at most 60% by weight, or at most 58% by weight, or at most 56% by weight, or at most 54% by weight, or at most 52% by weight, or at most 50% by weight of repeating units derived from alkyl (meth)acrylate monomers.
[0065] Based on the total weight of the PCE copolymer, the PCE copolymer contains 5% to 40% by weight of repeating units derived from "PEG monomer". The PEG monomer contains (i) a (meth)acrylate moiety linked via an ester bond to (ii) a polyethylene glycol moiety containing an average of more than one ethylene oxide unit, and (iii) a terminal portion of the polyethylene glycol moiety linked at an end opposite to the (meth)acrylate moiety, the terminal portion being selected from hydrogen or alkyl moieties. Formula 1 illustrates an exemplary PEG monomer:
[0066]
[0067] in:
[0068] • Each R 1 Independently a hydrogen or alkyl group, wherein the alkyl group is selected such that R 1 On average, it contains fewer than 2 carbon atoms;
[0069] • Each R 2 Independently a terminal portion selected from hydrogen or alkyl groups; and
[0070] • As previously described, each R 3 Independently hydrogen or a lower alkyl group, the lower alkyl group being selected such that R 3 On average, it contains less than 0.5 carbon atoms;
[0071] • It is the polyethylene glycol (PEG) portion as previously described, which contains n repeating epoxide units, where n is greater than 1 on average.
[0072] In some embodiments, the meth(acrylate) moiety of the PEG monomer primarily comprises (greater than 50% by weight) the acrylate moiety (R... 1 =H). In some embodiments, the meth(acrylate) moiety of the PEG monomer primarily comprises (greater than 50% by weight) the methacrylate moiety (R). 1 =-CH3). In some implementations, R 1 On average, it contains at most 1.2 carbon atoms, at most 1.0 carbon atoms, at most 0.8 carbon atoms, at most 0.6 carbon atoms, at most 0.4 carbon atoms, or at most 0.2 carbon atoms. In some embodiments, R 1 On average, it contains at least 0.2 carbon atoms, at least 0.4 carbon atoms, at least 0.6 carbon atoms, at least 0.8 carbon atoms, or at least 1.0 carbon atoms.
[0073] Polyethylene glycol portion, R 3 The implementation schemes for n are as previously described.
[0074] The polyethylene glycol portion of the PEG monomer has an end portion (R) opposite to the methyl (acrylate) portion. 2 End capping. In some implementations, the end portion is a hydrogen atom (R... 2 =H). In some embodiments, the terminal portion is an alkyl group (R). 2 =alkyl). Terminal portion (R) 2 The alkyl group in ) contains at least one carbon atom. In some embodiments, the terminal portion (R) 2 The alkyl groups in the ) contain an average of at most 24 carbon atoms, at most 22 carbon atoms, at most 20 carbon atoms, at most 18 carbon atoms, or at most 16 carbon atoms. In some embodiments, the terminal portion (R) 2 The alkyl group in () is a lower alkyl group, meaning that the alkyl group contains, on average, less than 8 carbon atoms or at most 6 carbon atoms or at most 4 carbon atoms or at most 2 carbon atoms. In some embodiments, the terminal portion (R) 2 The alkyl groups in the PEG monomer are aliphatic alkyl groups, meaning that the alkyl groups contain an average of at least 8 carbon atoms, at least 10 carbon atoms, at least 12 carbon atoms, or at least 14 carbon atoms. In some embodiments, the terminal portion of the PEG monomer contains a mixture of lower alkyl groups and aliphatic alkyl groups.
[0075] In some embodiments, the PEG monomer is selected such that it is moderately hydrophilic but also moderately lipophilic, and that it interacts with the oil phase during emulsion polymerization. In some embodiments, the PEG monomer is selected such that the resulting PCE copolymer is insoluble in acidic aqueous media but soluble in alkaline aqueous media. PEG chains that contain virtually no propylene oxide or butane oxide units are generally hydrophilic. When the PEG monomer contains a number of repeating alkyl oxide units (e.g., when n averages at least 10, at least 15, or at least 20), in some embodiments, it can be achieved by adding R... 2 The PEG monomer has aliphatic end groups and / or is made more lipophilic by incorporating propylene oxide or butane oxide into the PEG chain. On the other hand, when the PEG monomer contains only a small number of alkylene oxide units (such as when n averages at most 10, 15, or 20), in some embodiments the PEG chain contains almost no propylene oxide or butane oxide, and / or the terminal portion (R... 2 It contains hydrogen or lower alkyl groups.
[0076] In some embodiments, the PEG monomer has a number average molecular weight of at least 150 g / mol, at least 200 g / mol, at least 300 g / mol, at least 400 g / mol, at least 450 g / mol, or at least 500 g / mol. In some embodiments, the PEG monomer has a number average molecular weight of at most 3000 g / mol, at most 2000 g / mol, at most 1000 g / mol, at most 900 g / mol, at most 800 g / mol, or at most 750 g / mol.
[0077] In some embodiments, the PCE copolymer contains at least 6 wt%, at least 8 wt%, at least 10 wt%, at least 12 wt%, or at least 13 wt% of repeating units derived from PEG monomers. In some embodiments, the PCE copolymer contains at most 38 wt%, at most 35 wt%, at most 30 wt%, at most 25 wt%, at most 20 wt%, at most 18 wt%, at most 16 wt%, or at most 14 wt% of repeating units derived from PEG monomers.
[0078] PCE copolymers may optionally contain 0% to 20% by weight of repeating units derived from other olefinically unsaturated comonomers. Examples of suitable other comonomers include maleic acid, itaconic acid, styrene, vinyl acetate, vinyl alcohol, acrylonitrile, acrylamide, alkylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, sodium styrene sulfonate, sodium vinyl sulfonate, ethyl methacrylate, and vinyl chloride. In some embodiments, the PCE copolymer contains up to 15% by weight, up to 10% by weight, up to 5% by weight, up to 3% by weight, or up to 2% by weight of repeating units derived from other comonomers. In some embodiments, the PCE copolymer may be substantially free of repeating units derived from other comonomers (0% by weight).
[0079] Suitable (meth)acrylic acid monomers, (meth)acrylic acid alkyl ester monomers, PEG monomers, and other comonomers are commercially available. PEG monomers can also be prepared by known methods, such as the reaction of (meth)acryloyl chloride with polyethylene glycol as described in the following literature: Lin-Gibson et al., “Synthesis and Characterization of PEGDimethacrylates and Their Hydrogels”, 5(4). Biomacromolecules 1280–1287 (2004) and Takeshita et al., “Crystallization of graft copolymers 1.Graft Chains Misciblewith Main Chains” 42 Polymer Journal482–488 (2010).
[0080] In some embodiments, the PCE copolymer is a random copolymer. In some embodiments, the PCE copolymer satisfies formula 2:
[0081]
[0082] in:
[0083] • As previously described, each R is independently an alkyl group derived from a repeating unit of a (meth)acrylate monomer;
[0084] • As previously described, each R 1 Independently a hydrogen or alkyl group;
[0085] • As previously described, each R 2 Independently a terminal group;
[0086] •-(CR 3 H-CH2O) n - is the polyethylene glycol portion as previously described, which contains n repeating epoxy alkyl units;
[0087] • As described above, each R 3 Independently, it is hydrogen or a lower alkyl group;
[0088] • Each M is independently a substituent for a comonomer suitable for use in PCE copolymers, such as a hydroxyl moiety, amide moiety, alkylamide moiety, nitrile moiety, halide moiety, acetate moiety, organic sulfonate moiety, or organic phosphate moiety;
[0089] •x represents the number of repeating units derived from (meth)acrylic acid monomers, averaging 10% to 60% by weight of the polymer;
[0090] •y represents the number of repeating units derived from (meth)acrylate monomers, averaging 30% to 70% by weight of the polymer;
[0091] •z represents the number of repeating units derived from the PEG monomer, averaging 5% to 40% by weight of the polymer;
[0092] •m represents the number of repeating units derived from other monomers, averaging from 0% to 20% by weight of the polymer; and
[0093] • End groups on the polymer backbone are not shown.
[0094] In some embodiments of Equation 2, the repeating units shown are randomly distributed within the polymer. R, R... 1 R2 R 3 Implementation schemes for M, x, y, z, n, and m.
[0095] As shown in Formula 2, the PCE copolymer comprises a poly(carboxylic acid) polymer backbone (“acid polymer backbone”). The dangling alkyl groups and polyethylene glycol (PEG) moieties are linked to the acid polymer backbone via ester bonds. As previously described, this structure is sometimes referred to as a “comb” structure.
[0096] As previously described, the dangling alkyl and polyethylene glycol (PEG) moieties can be removed from the acidic polymer backbone of a PCE copolymer by hydrolysis to obtain a poly(carboxylic acid) polymer, referred to as a "hydrolysis product polymer" or "HPP". An example of HPP is shown in Formula 3:
[0097]
[0098] Where x, y, z, m, M and R 1 The values correspond to those in the PCE copolymer, and the end groups on the polymer backbone are not shown. The expected molecular weight distribution of HPP is approximately equal to the stoichiometric distribution of the acidic polymer backbone in the PCE copolymer.
[0099] The molecular weight of the acidic polymer backbone in the PCE copolymer can be conveniently measured by (1) hydrolyzing the PCE copolymer to recover HPP, and (2) performing size exclusion chromatography (SEC) analysis of HPP in an aqueous medium as described in the test method. HPP is generally soluble in aqueous media and is similar to commercially available acrylic acid standards.
[0100] Alternatively, the molecular weight of the acidic polymer backbone in the PCE copolymer can be measured by (1) hydrolyzing the PCE copolymer to recover HPP and (2) performing SEC analysis on the HPP in a tetrahydrofuran / formic acid solution as described in the test method. For some HPPs, SEC analysis in tetrahydrofuran / formic acid solution can provide clearer resolution of the molecular weight peaks corresponding to the HMW and LMW components than aqueous SEC analysis.
[0101] Alternatively, the molecular weight of some embodiments of the PCE copolymer can be directly analyzed by SEC analysis in a tetrahydrofuran / formic acid solution, as described in the test methods. In some embodiments, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, at least 95 wt%, or up to 100 wt% of the PCE copolymer is soluble in a tetrahydrofuran / formic acid (THF-FA; 100 / 5 volume / volume ratio) solution at a concentration of about 1 mg / mL. Similarly, for some PCE copolymers, SEC analysis in a tetrahydrofuran / formic acid solution can provide clearer resolution of molecular weight peaks corresponding to the HMW and LMW components than aqueous SEC analysis.
[0102] The molecular weights in this document are based on test methods that provide relative molecular weight determinations by comparison with known standards. Different test methods or different standards are known to determine different molecular weights for the same polymer. For absolute molecular weights, fractions recovered from SEC analysis can be analyzed using a multi-angle light scattering (MALS) detector according to known procedures.
[0103] As previously described, for the PCE copolymer of this invention, HPP has a multi-peak molecular weight distribution. HPP contains at least a higher molecular weight (HMW) component and a lower molecular weight (LMW) component. In some embodiments, SEC analysis of different molecular weight fractions of HPP shows two or more distinct peaks with a minimum value between them, the distinct peaks indicating the presence of both HMW and LMW components. In other embodiments, SEC analysis shows a main peak with a higher or lower molecular weight shoulder or tail; a shoulder or tail indicates the presence of both components even if a minimum value cannot be measured between their peaks. We assume that the presence of HMW and LMW components in HPP indicates that the corresponding PCE copolymer has both HMW and LMW components, wherein:
[0104] • Higher molecular weight (HMW) components include longer-chain, higher molecular weight main-chain polymers; and
[0105] • Lower molecular weight (LMW) components contain shorter, lower molecular weight polymer backbones.
[0106] In some embodiments, (1) the higher molecular weight (HMW) component of HPP has a weight-average molecular weight (M) greater than 200 kg / mol. w ), and (2) the lower molecular weight (LMW) component of HPP has a weight-average molecular weight (M) of less than 200 kg / mol. w In some implementations, the M of the HMW component of HPP wThe concentration is at least 250 kg / mol, or at least 300 kg / mol, or at least 350 kg / mol, or at least 400 kg / mol, or at least 450 kg / mol, or at least 500 kg / mol, or at least 550 kg / mol. In some embodiments, the M of the HMW component of HPP... w The maximum is 5000 kg / mol or 2000 kg / mol or 1500 kg / mol or 1200 kg / mol or 1000 kg / mol or 900 kg / mol or 800 kg / mol or 750 kg / mol.
[0107] In some implementations, the M of the LMW component of HPP w The maximum concentration is 180 kg / mol, 150 kg / mol, 120 kg / mol, 100 kg / mol, 80 kg / mol, 70 kg / mol, 65 kg / mol, 60 kg / mol, 55 kg / mol, 50 kg / mol, or 45 kg / mol. In some embodiments, the M of the LMW component of HPP is... w It is at least 10 kg / mol or at least 12 kg / mol or at least 15 kg / mol or at least 16 kg / mol or at least 17 kg / mol.
[0108] In some embodiments, the HMW component of HPP has a dispersion (Mw) of at least 4.0, at least 5.0, at least 6.0, at least 6.5, or at least 7.0. w / M n This is also known as the polydispersity index or molecular weight distribution. In some embodiments, the HMW component of the HPP has a dispersity of up to 15, up to 12, up to 11, or up to 10. In some embodiments, the LMW component of the HPP has a dispersity of at least 1.5, at least 1.8, at least 2.0, at least 2.2, or at least 2.3. In some embodiments, the LMW component of the HPP has a dispersity of up to 5.0, at most 4.0, at most 3.8, or at most 3.5.
[0109] In some implementations of HPP, the weight-average molecular weight (M) of the higher molecular weight (HMW) component is... w Compare the weight-average molecular weight (M) of the low molecular weight (LMW) components. wThe weight-average molecular weight (Mb / mol) of the higher molecular weight (HMW) component is at least 50 kg / mol, or at least 75 kg / mol, or at least 100 kg / mol, or at least 125 kg / mol, or at least 150 kg / mol, or at least 175 kg / mol, or at least 200 kg / mol, or at least 250 kg / mol, or at least 300 kg / mol, or at least 350 kg / mol, or at least 400 kg / mol. In some embodiments of HPP, the weight-average molecular weight (Mb / mol) of the higher molecular weight (HMW) component is at least 50 kg / mol, or at least 75 kg / mol, or at least 100 kg / mol, or at least 125 kg / mol, or at least 150 kg / mol, or at least 175 kg / mol, or at least 200 kg / mol, or at least 250 kg w Compare the weight-average molecular weight (M) of the low molecular weight (LMW) components. w (Up to 1000 kg / mol, or up to 900 kg / mol, or up to 850 kg / mol, or up to 800 kg / mol.)
[0110] In some embodiments, the HPP of the complete PCE copolymer has a dispersion of at least 5.0, at least 5.5, at least 6.0, at least 6.5, at least 7.0, at least 7.5, or at least 8.0. In some embodiments, the HPP of the complete PCE copolymer has a dispersion of at most 18, at most 15, at most 13, or at most 12.
[0111] In some embodiments, when measured in a tetrahydrofuran / formic acid solution according to a test method, the PCE copolymer has a number-average molecular weight (Mn) of at least 25 kg / mol, at least 30 kg / mol, or at least 35 kg / mol. n In some embodiments, when measured in a tetrahydrofuran / formic acid solution according to a test method, the PCE copolymer has a weight-average molecular weight (Mg) of at least 200 kg / mol, at least 300 kg / mol, at least 400 kg / mol, at least 500 kg / mol, at least 750 kg / mol, or at least 1000 kg / mol. w In some embodiments, when measured in a tetrahydrofuran / formic acid solution according to a test method, the PCE copolymer has a dispersion (M0) of at least 6.0 or at least 8.0 or at least 9.0 or at least 10 or at least 12 or at least 15 or at least 20 or at least 25 or at least 30. w / M n In some embodiments, when measured in a tetrahydrofuran / formic acid solution according to a test method, the PCE copolymer has a dispersion of up to 70, up to 60, or up to 50.
[0112] Note that the molecular weight data for the PCE copolymer applies only to the portion of the PCE copolymer soluble in a solution of tetrahydrofuran / formic acid (100 / 5 volume / volume ratio) at a concentration of approximately 1 mg / mL. The molecular weight of the insoluble substance was not measured using an SEC apparatus. In some embodiments, at least 50% by weight, or at least 55% by weight, or at least 60% by weight, or at least 65% by weight, or at least 70% by weight, or at least 75% by weight, or at least 80% by weight of the PCE copolymer is soluble.
[0113] In some embodiments, the HPP of the PCE copolymer comprises at least 20 wt%, at least 30 wt%, at least 40 wt%, at least 45 wt%, at least 55 wt%, at least 60 wt%, or at least 65 wt% of HMW component based on the total weight of HPP. In some embodiments, the HPP of the PCE copolymer comprises at most 90 wt%, at most 85 wt%, at most 80 wt%, at most 75 wt%, at most 70 wt%, at most 65 wt%, at most 60 wt%, at most 55 wt%, or at most 52 wt% of HMW component based on the total weight of HPP. In some embodiments, the HPP of the PCE copolymer comprises at least 5 wt%, at least 10 wt%, at least 15 wt%, at least 20 wt%, at least 25 wt%, at least 30 wt%, at least 35 wt%, at least 40 wt%, at least 45 wt%, or at least 48 wt% of LMW component based on the total weight of HPP. In some embodiments, the HPP of the PCE copolymer comprises up to 52% by weight, up to 50% by weight, up to 45% by weight, up to 40% by weight, or up to 35% by weight of LMW component based on the total weight of the HPP. In some embodiments, the PCE copolymer has a similar HMW component and LMW component ratio as described for HPP.
[0114] In some embodiments, when measured in a tetrahydrofuran / formic acid solution according to a test method, the PCE copolymer comprises an HMW component with a weight-average molecular weight of at least 200 kg / mol, at least 300 kg / mol, at least 400 kg / mol, at least 500 kg / mol, at least 600 kg / mol, at least 700 kg / mol, at least 800 kg / mol, or at least 900 kg / mol. In some embodiments, this HMW component constitutes at least 40% by weight, at least 45% by weight, at least 50% by weight, at least 55% by weight, at least 60% by weight, or at least 65% by weight of the PCE copolymer.
[0115] In some embodiments, the HPP is bimodal, and the HMW and LMW components are the only molecular weight-based components of the HPP. In some embodiments, the PCE copolymer is bimodal, and the HMW and LMW components are the only molecular weight-based components of the PCE copolymer.
[0116] In some embodiments, the HPP of the PCE copolymer also includes a weight-average molecular weight (M). w The medium molecular weight (MMW) component is greater than the LMW component but less than the HMW component. In some embodiments, the HPP of the PCE copolymer contains up to 25% by weight, up to 20% by weight, up to 15% by weight, up to 10% by weight, up to 5% by weight, or 0% by weight of the MMW component based on the total weight of the poly(carboxylic acid). In some embodiments, the PCE copolymer has an MMW component in a similar ratio to that described for HPP.
[0117] In some embodiments, the LMW component of the PCE copolymer is generated by using a chain transfer agent during the polymerization of the LMW component. In this case, at least one end of the acidic polymer backbone in the LMW component can be capped by residues of the chain transfer agent. For example, the PCE copolymer in the LMW component can conform to Formula 4:
[0118]
[0119] Where A is a residue of the chain transfer agent, and all other parts have the meaning defined for Equation 2.
[0120] In some implementations, A is derived from formula (-SR) 4 ) indicates that R 4 It contains a hydrogen or aliphatic moiety. In some embodiments, R 4 It is hydrogen. In some implementations, R 4 The hydrocarbon group moiety, such as an alkyl group. In some embodiments, R 4 It contains oxygen, such as a ketone, carboxylic acid, or carboxylic acid ester moiety. In some embodiments, R 4 It contains at least two carbon atoms or at least three carbon atoms. In some embodiments, R 4 It contains at most 24 carbon atoms, or at most 20 carbon atoms, or at most 18 carbon atoms, or at most 16 carbon atoms, or at most 14 carbon atoms, or at most 12 carbon atoms, or at most 10 carbon atoms, or at most 8 carbon atoms, or at most 6 carbon atoms, or at most 4 carbon atoms. In some embodiments, A is derived from the formula (-OR 4 -R 4 -X or simply R 4 It means that R 4 As previously described, and X is a halogen, such as chlorine or iodine.
[0121] In some embodiments, the monomers are selected such that the PCE copolymer is alkali-soluble, meaning it is soluble in water at pH 10, as measured by the test method. The cementitious environment is alkaline. In some embodiments, the PCE copolymer dissolves in the cementitious mixture. In some embodiments, the PCE copolymer has a solubility of at least 1 g / 100 g in water at pH 10. In some embodiments, the PCE copolymer has a solubility of at least 10 g / 100 g, at least 20 g / 100 g, or at least 30 g / 100 g in water at pH 10. The solubility limits of some PCE copolymers may be difficult to measure because the viscosity of the solution increases with increasing PCE copolymer concentration.
[0122] In some embodiments, the monomers are selected such that the resulting PCE copolymer remains a stable dispersion in aqueous acidic environments, such as in water with a pH of at most 6.5, 5.5, 5.0, 4.5, 4.0, 3.5, or 3.0. The ability to remain a dispersion is influenced by the balance between the hydrophilic and lipophilic portions of the polymer. The selection and ratio of acids, acrylates, and PEG monomers can affect the hydrophilicity and lipophilicity of the PCE copolymer as previously described, as well as the PCE copolymer's ability to remain a stable dispersion.
[0123] The PCE copolymer of the present invention is prepared by emulsion polymerization. Emulsion polymerization is a well-known method and is described in many publications, such as... Emulsion Polymerization of Acrylic Monomers Published by Rohm and Haas Company (1966), available https: / / ia600709.us.archive.org / 35 / items / emulsionpolymeri00rohm / emulsionpolymeri00rohm.pdf Obtained; Lovell et al., Fundamentals of Emulsion Polymerization, 21 Biomacromolecules 4396−4441 (2020); and Juaregui, Thesis: Synthesis and Optimization of Emulsion Polymers published by California Polytechnic State University, San Luis Obispo (2016).
[0124] Emulsion polymerization is carried out in an aqueous medium containing a surfactant that acts as an emulsifier. The monomer and surfactant form a dispersed organic phase in the aqueous medium, and the polymerization is initiated by a free radical initiator or a redox initiator. As previously described, the selection and proportion of monomers in emulsion polymerization reflect their desired proportions in the resulting polymer. In some embodiments, the monomer emulsion contains at least 15% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 60% by weight, based on the total weight of the emulsion. In some embodiments, the monomer emulsion contains at most 70% by weight, or at most 60% by weight, or at most 50% by weight, based on the total weight of the emulsion.
[0125] An example of a suitable surfactant used as an emulsifier is the trademark DOWFAX. ™ and TRITON ™ Available commercially from The Dow Chemical Company. See, for example, "Solutions for Emulsion Polymerizations," published by Dow Chemical Company (2018). In some embodiments, the weight percentage of the emulsifier to the monomer is 0.1 wt%, or at least 0.2 wt%, or at least 0.5 wt%, or at least 1.0 wt%, or at least 1.5 wt%. In some embodiments, the weight ratio of the emulsifier to the monomer is at most 3.0 wt%, or at most 2.5 wt%, or at most 2.0 wt%.
[0126] Initiators for emulsion polymerization are known and commercially available. In some embodiments, the initiator is a water-soluble free radical initiator. Examples of free radical initiators include persulfates (such as ammonium persulfate and sodium persulfate) and water-soluble azo compounds, such as 2,2'-azobis[2-methylpropanediamine] dihydrochloride and 4,4'-azobis[4-cyanopentanoic acid]. In some embodiments, the initiator-to-monomer weight ratio is at least 0.05% by weight, at least 0.1% by weight, or at least 0.15% by weight. In some embodiments, the initiator-to-monomer weight ratio is at most 1.0% by weight or at most 0.5% by weight.
[0127] In many embodiments, emulsion polymerization is carried out at a temperature of at least 50°C, at least 60°C, at least 70°C, or at least 75°C. In many embodiments, emulsion polymerization is carried out at a temperature of at most 95°C or at most 90°C. Pressure is not critical, as long as the blend of water, emulsifier, and other components is stable; in most embodiments, ambient pressure is convenient. In many embodiments, the reaction mixture is stirred to provide good mixing.
[0128] In some embodiments, the polymerization is catalyzed by a redox catalyst. Redox catalysts are commercially available and their use in the emulsion polymerization of acrylic monomers is known and disclosed in numerous references, such as... Emulsion Polymerization of Acrylic Monomers Published by Rohm and Haas (1966) and Sarac, “Redox Polymerization,” 24 Prog. Polym. Sci. 1149–1204 (1999).
[0129] Normal emulsion polymerization typically yields PCE copolymers with molecular weights corresponding to the HMW component. Polymerization of the LMW component (and optionally the MMW component) is carried out under conditions suitable for limiting polymer backbone growth. Known methods for controlling chain growth include the use of chain transfer agents, atom transfer radical polymerization (ATRP), reversible addition / fragmentation chain transfer polymerization (RAFT), or nitrile-oxygen mediated polymerization. See, for example, Cunningham, “Living / Controlled Radical Polymerizations in Dispersed Phase Systems,” 27 Pro, Poly, Sci. 1039-1067 (2002) and “Sigma-Aldrich Controlled Radical Polymerization Guide,” published by Merck KGaA (2019).
[0130] In some implementations, the LMW component is polymerized in the presence of a chain transfer agent. Chain transfer agents and their uses are well known. See, for example, K. Matyjaszewski and T. Davis, Handbook of Radical Polymerization Chapter 12, “Control of Free Radical Polymerization by ChainTransfer Methods” 629-691 (2002). Examples of suitable chain transfer agents include thiols, disulfides, alcohols, and haloalkyl compounds. In some embodiments, the chain transfer agent is represented by Formula 5:
[0131]
[0132] Where R 4 As previously described. Examples of suitable chain transfer agents are methyl mercaptopropionate, octyl mercaptohydride, and dodecyl mercaptohydride, which are commercially available.
[0133] The amount of chain transfer agent is suitable for limiting the growth of the acidic polymer backbone as previously described. In some embodiments, the polymerization of the LMW component is carried out in the presence of at least 0.4 wt%, at least 0.5 wt%, at least 0.6 wt%, at least 0.7 wt%, at least 0.8 wt%, at least 0.9 wt%, or at least 1.0 wt% of chain transfer agent based on the total weight of monomers in the reaction mixture. In some embodiments, the polymerization of the LMW component is carried out in the presence of at most 5.0 wt%, at most 4.0 wt%, at most 3.0 wt%, at most 2.0 wt%, at most 1.8 wt%, at most 1.6 wt%, at most 1.4 wt%, or at most 1.2 wt% of chain transfer agent based on the total weight of monomers in the reaction mixture. In some embodiments, the polymerization of the HMW component is carried out in the presence of at most 1.0 wt%, at most 0.5 wt%, at most 0.3 wt%, at most 0.1 wt%, or 0 wt% of chain transfer agent based on the total weight of monomers in the reaction mixture.
[0134] At least one HMW component and at least one LMW component can be polymerized separately, and then the HMW and LMW components can be physically blended to form a multimodal PCE copolymer. Alternatively, the HMW and LMW components can be polymerized sequentially in the same reaction mixture. In some embodiments, the HMW component is first prepared by polymerizing a first portion of monomers under conditions suitable for forming the HMW component, and then the LMW component is prepared by polymerizing a second portion of monomers in a mixture of products from the HMW polymerization under conditions suitable for forming the LMW component. In some embodiments, the LMW component is first prepared by polymerizing a first portion of monomers under conditions suitable for forming the LMW component, and then the HMW component is prepared by polymerizing a second portion of monomers in a mixture of products from the LMW reaction under conditions suitable for forming the HMW component. In some cases, it may be simpler to prepare the HMW component first because if the LMW component process is performed first, residual chain transfer agents may enter the HMW component process and negatively affect the molecular weight of the HMW component.
[0135] In some embodiments, the monomer mixture used to polymerize the HMW component and the LMW component contains similar monomers in similar proportions, such that the resulting HMW component and LMW component have similar polymer compositions. In some embodiments, the monomer mixture used to polymerize the HMW component and the LMW component contains different monomers and / or different monomer proportions, such that the resulting HMW component and LMW component have different polymer compositions.
[0136] The product of emulsion polymerization is an aqueous dispersion containing polymer particles comprising a PCE copolymer suspended in an aqueous medium. In some embodiments, the z-mean diameter of the polymer particles is at least 10 nm, at least 25 nm, at least 50 nm, at least 70 nm, or at least 90 nm. In some embodiments, the z-mean diameter of the polymer particles is at most 1200 nm, at most 1000 nm, at most 800 nm, at most 600 nm, at most 500 nm, at most 250 nm, at most 150 nm, or at most 100 nm. In some embodiments, the aqueous dispersion is a colloidal dispersion.
[0137] In some implementations, the aqueous dispersion produced by polymerization can be modified, such as by adding water or other solvents, by adding dispersants or other additives, or by adding acids, bases or buffers to adjust the pH.
[0138] The aqueous medium in the aqueous dispersion contains at least 50% by weight of water based on the weight of the aqueous medium. In some embodiments, the aqueous medium contains at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight, or at least 95% by weight, or 100% by weight of water based on the weight of the aqueous medium. Other components of the aqueous medium, if any, should be miscible with water and should not cause the PCE copolymer particles to dissolve or become colloidally unstable in the aqueous medium.
[0139] In some embodiments, the aqueous dispersion has a pH of at most 6.0, at most 5.0, at most 4.5, at most 4.0, at most 3.5, or at most 3.0. In some embodiments, the aqueous dispersion has a pH of at least 1.8, at least 2.0, or at least 2.5. In some embodiments, the PCE copolymer becomes water-soluble at a pH of at least 7, at least 8, at least 9, or at least 10.
[0140] In some embodiments, the aqueous dispersion is stable at 25°C for at least 1 day, at least 1 week, at least 1 month, at least 2 months, at least 3 months, or at least 6 months. In this regard, "stable" means that the aqueous dispersion does not exhibit visible phase separation, particle aggregation, or agglomeration.
[0141] In some embodiments, the aqueous dispersion comprises at least 10 wt%, at least 15 wt%, at least 20 wt%, at least 25 wt%, at least 27 wt%, or at least 29 wt% of polymer particles based on the total weight of the aqueous dispersion. In some embodiments, the aqueous dispersion comprises at most 60 wt%, at most 50 wt%, at most 45 wt%, or at most 40 wt% of polymer particles based on the total weight of the aqueous dispersion.
[0142] In some implementations, the aqueous dispersion can be stored and used without recycling the PCE copolymer.
[0143] In some embodiments, the aqueous dispersion can be spray-dried to form a powder containing the PCE copolymer. Spray drying equipment is commercially available with its instruction manual, and spray drying is described in numerous publications, such as: Santos et al., “Spray Drying – A Overview,” available from: http: / / dx.doi.org / 10.5772 / intechopen.72247 ; "Spray Dry Manual" published by Bete Performance Spray Engineering on www.BETE.com; and "Review on Spray Drying Technology" by More Swati et al. 4(2) IJPCBS 219-225 (2014). PCE copolymer powder is easier to store and transport, and can optionally be added to the dry mixture before water is added.
[0144] Uses as a concrete additive
[0145] The multimodal PCE copolymer of the present invention is used as a water-retaining agent in cementitious mixtures (dry or wet mixtures). The powder containing the PCE copolymer can be added to the dry mixture before water is added. Alternatively, the powder or aqueous dispersion containing the PCE copolymer can be added to the wet mixture after water is added. Alternatively, the powder or aqueous dispersion containing the PCE copolymer can be added to water before water is added to the dry mixture.
[0146] Cementitious mixtures contain fillers, cement, and optional other additives as dry components. ("Dry component" refers to any component of a cementitious mixture that is normally solid at up to 40°C and atmospheric pressure.)
[0147] Fillers for cementitious mixtures typically contain inorganic particles. The particle size of the filler varies depending on the intended use of the cementitious mixture. Mortar, grout, and stucco fillers typically contain sand. US standards for masonry fillers are listed in ASTM C144 and AASHTO M 45-15 / ASTM C 144-11. Concrete fillers typically contain aggregates, mixtures of sand and gravel of various sizes. US standards for concrete aggregate fillers are listed in ASTM C33 and AASHTO M 6 / M 80. See also Kousmata et al. Design and Control of Concrete MixturesChapter 6, “Aggregates for Concrete” (2016). In some embodiments, the filler may also contain volcanic ash, such as fly ash, calcined kaolin, pumice, or pyrolytic silica; volcanic ash and its use in cementitious mixtures are well known and described in U.S. Patent 9,181,131,B2. In some embodiments, the filler may also contain inorganic pigments, such as titanium dioxide, other metal oxides, or carbon black. In some embodiments, the filler may also contain organic fibers or particles.
[0148] In some embodiments, the cementitious mixture, excluding water, contains at least 50% by weight, at least 60% by weight, at least 65% by weight, or at least 70% by weight of filler, based on the dry component. In some embodiments, the cementitious mixture, excluding water, contains at most 85% by weight or at most 80% by weight of filler, based on the dry component. In some embodiments, the cementitious mixture, excluding water, contains at least 50% by volume, at least 55% by volume, or at least 60% by volume of filler, based on the dry component. In some embodiments, the cementitious mixture, excluding water, contains at most 85% by volume, at most 80% by volume, or at most 75% by volume of filler, based on the dry component.
[0149] ASTM recognizes five types of cement: Type 1 (ordinary Portland cement); Type 2 (medium sulfate-resistant cement); Type 3 (rapid-hardening cement); Type 4 (low-heat cement); and Type 5 (high sulfate-resistant cement). Blends and variations of these five types are also available, such as Portland limestone cement (Type 1L). Any of these cements can be used in the cementitious mixtures of this invention. In some embodiments, the cement is ordinary Portland cement. In some embodiments, the cement is a variant of ordinary Portland cement, referred to as white cement. In some embodiments, the cement is Portland limestone cement. In some embodiments, the cement is a more specialized cement, such as high alumina cement or calcium sulfoaluminate cement. Suitable cements are commercially available.
[0150] The cementitious mixture should contain sufficient cement to effectively bind the dry components together. In some embodiments, based on the dry components and excluding water, the cementitious mixture contains at least 15% by weight or at least 20% by weight of cement. In some embodiments, based on the dry components and excluding water, the cementitious mixture contains at most 50% by weight or at most 40% by weight or at most 35% by weight or at most 30% by weight of cement.
[0151] Examples of other additives that may be optionally included in cementitious mixtures include water-retaining agents, starch ethers, rheology modifiers, air-entraining agents, accelerators, retarders, superplasticizers, and defoamers.
[0152] • Redispersible powders are organic polymer powders dispersed in a wet mixture and impart improved flexibility and toughness to the cured cementitious mixture. Some embodiments of redispersible powders include one or more of ethylene / vinyl acetate copolymers, vinyl acetate / vinyl tert-carbonate copolymers, and acrylic copolymers.
[0153] • Additional water-retaining agents, such as cellulose ethers, further slow the separation of water from the wet mixture. In some embodiments, the PCE copolymer is the sole water-retaining agent in the cementitious mixture. In some embodiments, the cementitious mixture also contains additional water-retaining agents. In some embodiments, the weight ratio of the PCE copolymer to the additional water-retaining agent is at least 1:4, at least 1:3, at least 1:2, or at least 1:1. In some embodiments, the weight ratio of the PCE copolymer to the additional water-retaining agent is at most 9:1, at most 4:1, at most 3:1, at most 2:1, or at most 1:1.
[0154] • Starch ethers (such as hydroxypropyl starch ether) can improve the anti-sagging and anti-slip properties of wet mixtures, as well as extend drying time and provide a smoother surface.
[0155] • Rheology modifiers, such as bentonite, organically modified clay, palygorskite, pyrolytic silica, and precipitated calcium carbonate, can alter the viscosity and shear-thinning behavior of wet mixtures.
[0156] • Air-entraining agents create small air bubbles in wet mixtures, which improves the resilience of cured mixtures under freeze-thaw cycles. Air-entraining agents are often surfactants.
[0157] • Accelerators speed up the solidification of wet mixtures. They are particularly useful in cold weather environments. Examples of common accelerators include calcium nitrate, calcium nitrite, calcium formate, and certain aluminum compounds.
[0158] • Retarder slows down the setting time of wet mixtures. Examples of common retarders include lignin sulfonic acid, hydroxycarboxylic acid, carbohydrates, lead oxide, zinc oxide, phosphates, borates, and calcium, sodium, and ammonium salts of fluorides.
[0159] • Superplasticizers can be used to produce and utilize wet mixtures with low moisture content. Examples of supplemental superplasticizers include sulfonated melamine-formaldehyde condensates, sulfonated naphthalene-formaldehyde condensates, modified lignin sulfonates, and polycarboxylic acid ethers. Superplasticizer formulations with instructions for use are commercially available.
[0160] • Defoamers reduce air introduction and voids in wet mixtures. Examples of defoamers include mineral oils, polyethylene glycol, and polyether siloxanes. In some embodiments, the wet mixture contains at least 10 ppm, at least 25 ppm, at least 40 ppm, or at least 50 ppm of defoamer based on the total weight of the wet mixture. In some embodiments, the wet mixture contains at most 500 ppm, at most 200 ppm, at most 100 ppm, or at most 75 ppm of defoamer based on the total weight of the wet mixture.
[0161] The aforementioned additives are commercially available along with their instructions for use.
[0162] In some embodiments, based on the dry component and excluding water, the cementitious mixture contains up to 10% by weight, up to 5% by weight, or up to 2% by weight of other additives. In some embodiments, based on the weight of the dry component excluding water, the cementitious mixture contains an immeasurable amount (essentially 0% by weight) or at least 1% by weight or at least 2% by weight of other additives.
[0163] The cementitious mixture contains an amount of the PCE copolymer of the present invention suitable for reducing or preventing water separation from the wet mixture. In some embodiments, the cementitious mixture contains at least 0.05 wt%, at least 0.08 wt%, at least 0.10 wt%, at least 0.1 wt%, at least 0.15 wt%, at least 0.2 wt%, at least 0.25 wt%, or at least 0.3 wt% of PCE copolymer based on the total weight of cement. In some embodiments, the cementitious mixture contains at most 1.0 wt%, at most 0.8 wt%, at most 0.6 wt%, at most 0.5 wt%, at most 0.4 wt%, or at most 0.3 wt% of PCE copolymer based on the total weight of cement.
[0164] In some implementations, the multimodal PCE copolymer acts as both a water-retaining agent and a water-reducing agent (superplasticizer). We assume, without constraint, that the HMW component has a stronger effect on water retention than the LMW component, and that the LMW component has a stronger effect on water reduction than the HMW component. Depending on the desired performance of the multimodal PCE, it may be desirable to select blends with HMW and LMW components in proportions higher or lower than specified ranges.
[0165] In some embodiments, based on the dry component weight and excluding water, the cementitious mixture contains at most 0.15 wt%, at most 0.1 wt%, at most 0.08 wt%, at most 0.05 wt%, at most 0.02 wt%, or at most 0.01 wt% of cellulose ether. In some embodiments, the cementitious mixture is substantially free of cellulose ether (0 wt%). In some embodiments, the cementitious mixture contains at least 0.01 wt% of cellulose ether.
[0166] In some embodiments, based on the dry component weight and excluding water, the cementitious mixture contains up to 0.15 wt%, up to 0.1 wt%, up to 0.08 wt%, up to 0.05 wt%, up to 0.02 wt%, or up to 0.01 wt% of supplemental superplasticizer. In some embodiments, the cementitious mixture is substantially free of supplemental superplasticizer (0 wt%).
[0167] In some embodiments, some or all of the dry components are pre-blended to form a dry mixture before being mixed with water to form a wet mixture. In some embodiments, some dry components, particularly additives, may be omitted from the dry mixture and may be added to water before being blended to form a wet mixture, or may be added to the wet mixture after it has been formed.
[0168] To prepare the wet mixture, water is blended with the dry components in an amount sufficient to completely wet them, providing a homogeneous cementitious mixture with desired workability and viscosity. The optimal amount of water varies depending on the dry components and their intended use, and can be readily determined experimentally. In some embodiments, the amount of water is at least 10% by weight, at least 15% by weight, at least 18% by weight, or at least 20% by weight, based on the total weight of the wet mixture. In some embodiments, the amount of water is at most 30% by weight, at most 25% by weight, at most 22% by weight, or at most 20% by weight, based on the total weight of the wet mixture.
[0169] In some implementations, when measured according to the test method, the wet mixture has a water retention rate of at least 92%, at least 94%, at least 95%, at least 96%, at least 97%, or at least 98%. There is no maximum expected water retention rate, but in many cases, a water retention rate exceeding 99% is unnecessary.
[0170] The wet mixture can be used in any suitable application. For example:
[0171] • Wet concrete mixtures can be cured in molds or templates to form solid structures such as pavements, paving materials, floors, blocks, walls, columns or other concrete products.
[0172] • Mortar can hold bricks, blocks, tiles or other structural elements in place.
[0173] • Plaster can be applied to walls or formed as a layer in exterior wall insulation and finishing systems (EIFS).
[0174] After application, the wet mixture is allowed to dry and cure. The time required for drying and curing varies significantly depending on the selection of dry components in the wet mixture (such as cement, accelerators, and retarders), the amount of water, the thickness of the application, and the temperature and humidity during drying and curing. In many implementations, cementitious mixtures are touch-dry in a few hours or less and can bear weight within a day or two. On the other hand, curing to full strength may take many days.
[0175] Upon completion of curing, the cured cementitious mixture reflects the content of the wet mixture used to prepare it. The cured cementitious mixture contains filler, cured cement, optional additives, and residual PCE copolymers of the present invention or their reaction products. In some embodiments, the alkaline environment of the wet mixture hydrolyzes the ester bonds in the PCE copolymer and releases PEG side chains. Therefore, some or all of the PEG side chains can be removed from the PCE copolymer. The released PEG polymer can migrate to other parts of the wet mixture and can be trapped there in the cured cementitious mixture. Similarly, some or all of the acidic polymer backbone can have its side chains partially or completely removed, and it contains a higher level of dangling acid moiety than the original PCE copolymer.
[0176] Test methods
[0177] Unless otherwise stated, the measurements listed in this application are performed using the following test methods:
[0178]
[0179] HPP was obtained by hydrolysis of PCE copolymer. :
[0180] The PCE copolymer powder sample was hydrolyzed in a Parr Bomb (#4749) container to obtain the corresponding HPP. Hydrolysis was performed by adding approximately 0.50 g of PCE copolymer, 1 g of potassium hydroxide pellets, 0.25 g of DI water, and 10 mL of ethanol to a Teflon cup. The Teflon cup was placed inside the Parr Bomb container and sealed according to the manufacturer's instructions. The sealed container was placed in an oven at 150°C for 3 days. The resulting sample was cooled to room temperature and the supernatant was decanted. The resulting HPP solids were collected in the container, rinsed with 10 mL of ethanol, and allowed to dry at room temperature.
[0181] Aqueous SEC Measurement of HPP Molecular Weight :
[0182] Prepare a sample of HPP solution. Mix HPP at a concentration of 2 mg / g in a phosphate buffer aqueous solution (20 mM, pH 7.0). Stir the sample overnight on a mechanical shaker at room temperature to completely dissolve the HPP. Next, filter the sample solution using a 0.2 μm Target2 (Fisher) PVDF filter. Visually inspect the sample to ensure that no undissolved material is present.
[0183] SEC analysis was performed using a Waters UPLC system equipped with an isocratic pump, degasser, injector, column oven, and a differential refractive index (RI) detector operating at 35°C. The UPLC system was equipped with TOSOH Bioscience TSKgel G2500PWxl and TSKgel GMPWxl columns (packed with 7 μm and 13 μm particles and internal dimensions of 7.8 mm × 300 mm). The system was calibrated using sixteen narrow-dispersion sodium polyacrylates from Mp=216 Da to Mp=1,100,000 Da, obtained from American Polymer Standards Corporation. 20 μL of sample was injected, and the mobile phase flow rate was maintained at 1.0 mL / min. Data were collected and processed using Empower software version 3 (Waters, Milford, MA). Note: This system provides relative molecular weight data based on the standards used in calibration, not absolute molecular weight data.
[0184] SEC measurements of solubility in organic solvents and molecular weight of organically soluble PCE copolymers.
[0185] The PCE copolymer sample was dissolved in a tetrahydrofuran / formic acid (THF-FA; 100 / 5 v / v ratio) solution at a concentration of approximately 1 mg / mL and filtered through an Acrodisc CR13 mm 0.45 μm PTFE filter. The molecular weight distribution of the polymer was determined by size exclusion chromatography (SEC). Analysis was performed using an Agilent 1200 series HPLC system equipped with a degasser, pump, autosampler, and UV-Vis and Wyatt T-rEX refractive index detectors operating at 35 °C. The system was equipped with Shodex KF-805L and KF807L columns (packed with 10 µm and 18 µm particles, respectively, with an ID length of 8 × 300 mm). The sample injection volume was 100 μL, the mobile phase was 100 / 5 v / v THF-FA, and the flow rate was 1.0 mL / min. The system was calibrated using narrow-dispersion polystyrene standards ranging from Mp=580Da to Mp=6,500,000Da obtained from Agilent Technologies. Data were collected using ASTRA 7 software and processed using ASTRA 8 software. The mass of recovered polymer was calculated based on the polymer peak area using the refractive index detector reaction, RI detector calibration, and an estimated dn / dc = 0.084 mL / g. No insoluble polymer was recovered, and the percentage of solvent-soluble polymer was shown by comparing the mass of the recovered polymer with the mass of 1 mg / mL of polymer mixed with the injected sample. Note: This system provides relative molecular weight data based on the standards used in calibration, not absolute molecular weight data.
[0186] Mortar preparation for testing
[0187] Use the following general procedure to prepare the mortar for testing.
[0188] 64.7 g of sand, 35.0 g of cement, and additives were mixed to produce a dry mixture. If PCE copolymers were added, they were added to the dry mixture as spray-dried powders. Water was added to the dry mixture to prepare a fresh mortar paste for application testing. The amounts of additives and water in the fluid mixture were selected such that the final wet mixture contained (1) the desired amount of additives and (2) the ratio of water to dry mixture in the mortar was approximately 0.22.
[0189] Except as explicitly stated in the specific test methods, wet mortar mixtures shall be prepared as follows:
[0190] 1. Add water to the dry mixture;
[0191] 2. Mix the sample for 30 to 60 seconds, until the wet mixture is smooth and homogeneous, without lumps;
[0192] 3. Let the sample stand for 3 minutes;
[0193] 4. Mix the sample for 1 minute;
[0194] 5. Allow the sample to stand for 4.5 minutes; and
[0195] 6. Mix the sample for 30 seconds.
[0196] Water retention rate test
[0197] Prepare the mortar as previously described. Place an aluminum ring in the center of a pre-weighed circular filter paper ring on a flat, non-absorbent surface. The ring has an inner diameter of 55 mm and a depth of 10 mm. The filter paper is Whatman 2294 grade filter paper with a diameter of 110 mm and a basis weight of 556 g / m³. 2 The ring completely fills the mortar sample; the sample weight is approximately 55g to 65g. Allow the sample to stand for 30 minutes. Remove the filter paper and weigh it to determine the water it has absorbed, and subtract the weight of the water in the filter paper from the initial water content in the mortar to obtain the water retention rate.
[0198] Mortar compressibility test
[0199] Prepare the mortar as previously described, except that in step 5 the mortar is left to stand for 7 minutes and step 6 is omitted.
[0200] Apply approximately 100g of mortar sample to an acrylic glass plate using a 1 / 4 inch x 1 / 4 inch notched trowel, keeping the trowel at a 60-degree angle to the substrate. o Inclined angle. After applying two coats, allow the mortar to dry for 10 minutes, then cover it with a 10cm x 10cm glass plate. Immediately place a 2.21kg weight on the plate for 30 seconds. Take images of the compressed mortar under a lightbox to quantify the mortar spread area and determine compressibility.
[0201] Example
[0202] The following examples illustrate specific implementations of the present invention, but do not limit the widest scope of the invention.
[0203] The materials in Table 1 are used in the examples:
[0204]
[0205] Synthesis of PCE 1-PCE5 (high molecular weight and low molecular weight PCE)
[0206] The monomers listed in Table 2 were emulsion polymerized according to the following process: SLS (12.60 g 28% by weight aqueous solution) and water (579.48 g) were placed in a 3L 4-necked round-bottom flask equipped with a water condenser, a top stirrer and a thermocouple, and placed under nitrogen and heated to 88°C.
[0207] Monomer emulsions were prepared by mixing SLS (8.40 g, 28% by weight aqueous solution) and water (195 g) together in a wide-mouth glass flask at ambient temperature. The desired monomers, as shown in Table 2, were added in the following order:
[0208] •(meth)acrylate monomers,
[0209] •PEG monomers,
[0210] • Methacrylic acid monomer (MAA) containing dissolved MMP (if present).
[0211] The monomer weight ratios for each embodiment were selected to reflect the proportions shown in Table 2, and the total mass of monomers was selected to provide a final PCE copolymer dispersion with the solids content shown in Table 2. A 41.8 g portion of monomer emulsion was added to a round-bottom flask while stirring. Immediately after adding the monomer emulsion, a mixture of APS initiator (0.53 g in 11.25 g water) was added to the vessel, followed by rinsing with water (3.75 g). At the exothermic peak, an aqueous APS solution (0.23 g in 45 g water) and the remaining monomer emulsion were added to the round-bottom flask over 1.5 hours while maintaining the contents at 85°C. After 1.5 hours, the container and feed line of the monomer emulsion and APS were rinsed with water, and the reaction mixture was stirred at 85°C for 5 minutes. An aqueous APS solution (0.19 g in 48.875 g water) was added over 15 minutes. The contents were cooled to 75°C, and dilution water (15 g) was added.
[0212] Continue cooling to 30°C, and during cooling, remove any remaining free monomers from the round-bottom flask by adding 0.15% active ferrous sulfate heptahydrate (2.74 g), followed by adding 70% tert-butyl hydroperoxide aqueous solution (0.3 g, diluted in 9.38 g of water) over 15 minutes and rinsing with water (1.988 g), and simultaneously adding isoascorbic acid (0.41 g, in 9.38 g of water) over 15 minutes and rinsing with additional water (1.988 g). Then, repeat the addition of tert-butyl hydroperoxide and isoascorbic acid as previously described.
[0213] This process yields an aqueous dispersion containing PCE copolymer particles suspended in an aqueous medium. The aqueous dispersion is continuously filtered through 100-mesh and 325-mesh sieves. The approximate solids content of the aqueous dispersion is shown in Table 2. The pH of the aqueous dispersion ranges from 2.5 to 4.
[0214] Dispersion samples of PCE1 to PCE5 were spray-dried to produce PCE copolymer powder. The aqueous dispersion was diluted to 15% to 20% wt% solids. The diluted dispersion was spray-dried using a GEA Mobile Miner spray dryer equipped with a dual-fluid nozzle atomizer. The inlet and outlet temperatures were set to 120°C–125°C and 55°C–65°C, respectively. The nitrogen (N2) pressure at the nozzle was set to 1 bar, and the flow rate was 50%, equivalent to an air flow rate of 6 kg / h. The diluted aqueous dispersion was introduced into the spray dryer via a peristaltic pump. The water content in the atomized droplets was rapidly evaporated by contact with the hot N2 stream at the inlet temperature. The dried powder was then cooled to the outlet temperature. A cyclone separator in the spray dryer separated the dried polymer powder from the N2 stream. Residual powder was filtered before aeration.
[0215] Dispersion samples of PCE1 to PCE5 were freeze-dried to produce PCE copolymer powder. Each dispersion was placed in a freezer at -20°C for 2 days, and then placed on a LABCONCO FreeZone 4.5L instrument at -50°C for 3 days, with the vacuum set to 0.01 Torr and the condenser set to -50°C.
[0216] Samples of each PCE copolymer powder were hydrolyzed and the molecular weight distribution of HPP was measured by aqueous SEC according to the method given in the test method. The results are shown in Table 2.
[0217]
[0218] PCE1-PCE5 were mixed with each other and then mixed with cellulose ether (Cel Eth 1) to prepare the mixtures shown in Table 3. The mixtures in IE3a to IE10 are bimodal PCE copolymers.
[0219] Synthesis of PCE 6 (one-pot bimodal molecular weight PCE)
[0220] SLS (8.4 g, 28% by weight aqueous solution) and water (386.25 g) were placed in a 2 L 4-necked round-bottom flask equipped with a water condenser, a top stirrer and a thermocouple, and placed under nitrogen and heated to 88 °C.
[0221] SLS (5.60 g, 28% by weight aqueous solution) and water (203.875 g) were stirred together in a wide-mouth glass flask as an aqueous carrier for monomer emulsions at ambient temperature. Two monomer emulsions (ME1 and ME2) were prepared.
[0222] ME1 is prepared by adding the following substances in the following order:
[0223] • 50% by weight of EA monomer,
[0224] • 13% by weight of MPEGMA500 single unit
[0225] • 37% by weight of methacrylic acid monomer.
[0226] ME2 is prepared by adding the following substances in the following order:
[0227] • 49% by weight of EA monomer, of which 1% by weight of MMP CTA is dissolved in the EA monomer prior to addition.
[0228] • 13% by weight of MPEGMA500 single unit
[0229] • 37% by weight of methacrylic acid monomer.
[0230] The organic content of the monomer emulsion is 70% by weight. ME1 accounts for 70% by weight of the monomer emulsion and ME2 accounts for 30% by weight of the monomer emulsion.
[0231] A portion of ME1 (27.45 g) was removed from ME1 and added to the reactor to start the process. Immediately after adding 27.45 g of ME1, a mixture of APS initiator (0.38 g in 7.50 g water) was added to the reactor, followed by rinsing with water (2.5 g). After the exothermic peak, an aqueous APS solution (0.15 g in 30 g water) and a monomer emulsion (ME1 feed completed, then ME2 feed started and completed) were gradually added to the round-bottom flask over 1.5 hours while maintaining the contents at 85°C. After 1.5 hours, the container and feed line of the monomer emulsion and APS were rinsed with water, and the reaction mixture was stirred at 85°C for 5 minutes. An aqueous APS solution (0.13 g in 32.5 g water) was added over 15 minutes. The contents were cooled to 75°C, and water (10.0 g) was added.
[0232] Continue cooling to 30°C, and during cooling, remove any remaining free monomers from the round-bottom flask by adding 0.15% active ferrous sulfate heptahydrate (1.83 g), followed by adding 70% tert-butyl hydroperoxide aqueous solution (0.2 g, diluted in 6.2 g water) over 15 minutes and rinsing with water (1.25 g), and simultaneously adding isoascorbic acid (0.28 g, in 6.25 g water) over 15 minutes and rinsing with additional water (1.25 g). Then, repeat the addition of tert-butyl hydroperoxide and isoascorbic acid once, as previously described.
[0233] This reaction process yields an aqueous dispersion containing bimodal PCE copolymer (PCE6) particles suspended in an aqueous medium. The aqueous dispersion is continuously filtered through 100-mesh and 325-mesh sieves. The approximate solids content of the aqueous dispersion is 31% by weight. The pH of the aqueous dispersion is 2.5 to 3.5.
[0234] The aqueous dispersions were spray-dried as described for PCE1-PCE5, and the powdered sample of PCE6 was recovered. The PCE6 powdered sample was hydrolyzed, and the molecular weight distribution of HPP was measured by aqueous SEC according to the method given in the test method. The results are shown in Table 2.
[0235] The PCE 6 powder sample was dissolved in a mixture of tetrahydrofuran and formic acid, and its molecular weight was measured as described in the test method. The mass recovery was 79.2% by weight. The number-average molecular weight of the recovered fraction was 38.3 kg / mol. The weight-average molecular weight of the recovered fraction was 1757 kg / mol. The dispersity of the recovered fraction was 46.0.
[0236] Applications in mortar
[0237] The mortars used for testing were prepared using the procedures outlined in the test method. The additives and their proportions in each mortar sample are shown in Table 3. The water retention and compressibility of the mortars were tested. The compressibility test demonstrates the workability of the mortars. The results are shown in Table 3.
[0238]
[0239] Examples IE1 to IE10 of this invention use multimodal PCE copolymers; all of them have a water retention rate of 95% or better and a compressibility of 68% to 100%. Comparative Examples CE2 to CE8 use unimodal PCE copolymers; their viscosity is too low or too high to be compressible, and some of them have a water retention rate far below 95%. Comparative Example CE1 has good water retention and sufficient compressibility, but uses a full 0.3% by weight of cellulose ether.
Claims
1. A multimodal poly(carboxylic acid ether) ("PCE") copolymer, said multimodal poly(carboxylic acid ether) ("PCE") copolymer comprising repeating units derived from: (a) 10 to 60 percent by weight of (meth)acrylic acid monomers; (b) 30 to 70 percent by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety comprises an average of 1 to 3.5 carbon atoms; and (c) 5% to 40% by weight of PEG monomers, each of which independently contains: (i) The (meth)acrylate moiety, which is linked via an ester bond to (ii) below. (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and (iii) A terminal portion of the polyethylene glycol portion connected at the end opposite to the (meth)acrylate portion, the terminal portion being selected from the hydrogen or alkyl portion; and (d) Other unsaturated monomers from 0 to 20% by weight Wherein (i) the weight percentage is based on the total weight of the PCE copolymer, (ii) the PCE copolymer comprises an acidic polymer backbone connected to a plurality of dangling polyethylene glycol side chains via ester bonds; and (iii) the hydrolysis of the ester bonds in the PCE copolymer produces a poly(carboxylic acid) polymer (referred to as "hydrolysis product polymer" or "HPP") with a multi-peak molecular weight distribution.
2. The PCE copolymer according to claim 1, wherein the HPP comprises (1) 20% to 95% by weight of a material having a weight-average molecular weight (M) greater than 200 kg / mol. w (2) 5% to 80% by weight of the HMW component, and (3) 5% to 80% by weight of the weight-average molecular weight (M) of less than 200 kg / mol. w The LMW component.
3. The PCE copolymer of claim 2, wherein the HPP comprises 45% to 95% by weight of the HMW component and 5% to 55% by weight of the LMW component.
4. The PCE copolymer according to claim 2, wherein (1) the weight-average molecular weight (M) of the HMW component of the HPP is... w (2) The weight-average molecular weight (M) of the LMW component of HPP is at least 300 kg / mol, and (3) The weight-average molecular weight (M) of the LMW component of HPP is at least 300 kg / mol. w The value is at most 100 kg / mol.
5. The PCE copolymer according to claim 2, wherein (1) the weight-average molecular weight (M) of the HMW component of the HPP is... w (2) The weight-average molecular weight (M) of the LMW component of the HPP is 350 kg / mol to 1500 kg / mol. w The concentration ranges from 10 kg / mol to 80 kg / mol.
6. The PCE copolymer according to claim 2, wherein the dispersion (M...) of the HPP... w / M n () should be at least 5.
0.
7. The PCE copolymer according to claim 2, wherein: (a) The weight-average molecular weight (M) of the HMW component of the HPP w The concentration ranges from 350 kg / mol to 1500 kg / mol, and (b) The weight-average molecular weight (M) of the LMW component of the HPP. w The concentration of 10 kg / mol to 80 kg / mol; and (c) The dispersion of the HPP (M w / M n () should be at least 5.
0.
8. The PCE copolymer according to any one of claims 1 to 7, wherein the PCE copolymer satisfies formula 2: in: (a) Each R is independently an alkyl group containing an average of 1 to 3.5 carbon atoms; (b) Each R 1 Independently a hydrogen or alkyl group, wherein the alkyl group is selected such that R 1 On average, it contains fewer than 2 carbon atoms; (c) Each R 2 Independently a hydrogen or alkyl group; (d)-(CHR 3 -CH2O) n - is the polyethylene glycol portion as previously described, the polyethylene glycol portion comprising n repeating epoxy alkyl units; (e) Each R 3 Independently, it is hydrogen or a lower alkyl group; (f) Each M is independently a hydroxyl moiety, amide moiety, alkylamide moiety, nitrile moiety, halide moiety, acetate moiety, organic sulfonate moiety, or organic phosphate moiety; (g)x represents the number of repeating units derived from (meth)acrylic acid monomers; (h)y represents the number of repeating units derived from (meth)acrylate alkyl ester monomers; (i)z represents the number of repeating units derived from the PEG monomer; (j)m represents the number of repeating units derived from other monomers; and (k) The end groups on the polymer backbone are not shown.
9. The PCE copolymer according to claim 8, wherein the PCE copolymer is a random copolymer.
10. The PCE copolymer according to claim 9, wherein: (a) Each R contains an average of 1.5 to 2.5 carbon atoms; (b) Each R 1 On average, it contains at most 1.2 carbon atoms; (c) Each R 3 It contains an average of 0.0 to 0.2 carbon atoms; (d)x corresponds to repeating units derived from (meth)acrylic acid monomers at a weight percentage of 25 to 45%. (e)y corresponds to repeating units derived from (meth)acrylate monomers at a weight percentage of 34 to 55%; (f)z corresponds to repeating units derived from PEG monomers ranging from 10 to 38 wt%. (g)m corresponds to repeating units derived from other unsaturated monomers at weight percentages of 0 to 2; (h)(1) n averages 4 to 15, and R 2 Contains 0 to less than 8 carbon atoms, or (2) n averages at least 15, and R 2 It contains at least 8 carbon atoms.
11. An aqueous dispersion comprising polymer particles suspended in an aqueous medium, wherein the polymer particles comprise the PCE copolymer according to claim 8.
12. The aqueous dispersion of claim 11, wherein the pH of the aqueous dispersion is from 2 to 5.
5.
13. A cementitious mixture comprising dry components (a)-(c): (a) Packing material; (b) Cement; (c) Based on the weight of the cement, at least 0.05% by weight of the PCE copolymer according to claim 8, And optionally, it also contains water.
14. The cementitious mixture of claim 13, wherein the cementitious mixture is a wet mixture containing 20 to 40 percent water by weight based on the weight of the dry components.
15. A method for preparing a poly(carboxylic acid ether) (PCE) copolymer, the method comprising the step of emulsion polymerization of the following substances in an aqueous medium: (a) 10% to 60% by weight of (meth)acrylic acid monomer; (b) 30% to 70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl moiety comprises an average of 1 to 3.5 carbon atoms; and (c) 5% to 40% by weight of PEG monomers, each of which independently contains: (i) The (meth)acrylate moiety, which is linked via an ester bond to (ii) below. (ii) Polyethylene glycol moieties containing an average of more than one ethylene oxide unit, and (iii) A terminal portion of the polyethylene glycol portion connected at the end opposite to the (meth)acrylate portion, the terminal portion being selected from the hydrogen or alkyl portion; and (d) up to 20% by weight of other unsaturated monomers The aqueous medium contains an emulsion amount of surfactant and polymerization initiator, wherein (i) the weight percentage is based on the total weight of monomers; (ii) the emulsion polymerization is carried out in at least two stages; and (iii) at least one stage of the polymerization is carried out in the presence of at most 0.1% by weight of chain transfer agent, and (ii) at least one stage of the polymerization is carried out in the presence of at least 0.4% by weight of chain transfer agent.
Citation Information
Patent Citations
Redispersible powder composition for dry mortar formulations
US9181131B2